PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA BADAN PERTANAHAN NASIONAL KOTA MEDAN - Sri Gustina Pane; Fatmawati Fatmawati (JRMB (Jurnal Riset Manajemen & Bisnis), 2018)
This study aims to investigate the effect of affective commitment, normative commitment and continuous commitment to the employees’ performance at the National Land Agency of Medan.The population of this study was 121 employees of the National Land Agency of Medan, whereas Slovin formula was used to determine 55 respondents as sample of the study. The questionnaire and documents were used as research instruments for data collection. This type of research was descriptive quantitative while the obtained data was analyzed through multiple linear regression and calculated by SPSS 20.  The hypothesis testing was performed by t test, F test and test of determination (R2). The results showed that the variables affective commitment, normative commitment and continuous commitment were significant positive effecting to the employees’ performance. The affective commitment obtained t-value 3,239 1,675 t-table and significant value 0.002 0.05, and normative commitment obtained t-value 2646 1675 with significant t-table 0.011 0.05, while continuos commitment obtained t-value 3,191 1,675 with significant t-table 0,002 0.05. Test F was used to know whether the mentioned variables had simultaneously effected to the employee performance, and the evidence was indicating that the value of F was 61 179 F table 3,179 with significant value 0.000 0.05. The analysis showed further that the affective commitment, normative commitment and continuous commitment influenced significantly to employee performance and it was in accordance with the test of determination (R2), was 0.770, or 77.0%, while the remaining was 23.0% and it could be from other factors which were not included in this research model.